USING EDUCATIONAL WEBSITES TO SUPPORT DIGITAL LEARNING: EDUTECH WORKSHOP FOR TEACHERS KEMAKMURAN II PUBLIC ELEMENTARY SCHOOL - Nur Laeli Asifah; Aliet Noorhayati Sustisno; Nur Fitriyasari; Nely Fathia; Nur Fajrina; Neng Siti Herliani (Jurnal Abdisci, 2026)
Abstract: Background. The rapid advancement of digital technology has encouraged the integration of digital learning platforms in schools; however, many elementary school teachers still have limited competence in utilizing educational websites effectively. Aim. This community service activity aimed to enhance teachers’ digital competencies through an EduTech Workshop focusing on the use of educational websites as learning support tools. Methods. The activity employed a Participatory Action Research approach involving 11 teachers of SD Negeri Kemakmuran II and was implemented through planning, action, and evaluation stages, including presentations, demonstrations, discussions, and hands-on practice using Rumah Pendidikan, Edcafe, Scratch, and Qreative.id. Results. The workshop achieved a 100% attendance rate, while 81.8% of participants actively engaged in discussions. All teachers successfully created digital evaluation questions using Edcafe and demonstrated improved understanding and skills in utilizing educational websites for teaching and learning activities. Conclusions. The EduTech Workshop effectively improved teachers’ digital literacy and readiness to implement technology-based learning in elementary education. Implication. This program can serve as a practical model for strengthening teachers’ digital competencies and supporting the ongoing digital transformation of education in elementary schools.